2024
DOI: 10.3847/1538-4357/ad4969
|View full text |Cite
|
Sign up to set email alerts
|

Cosmology with Multiple Galaxies

Chaitanya Chawak,
Francisco Villaescusa-Navarro,
Nicolás Echeverri-Rojas
et al.

Abstract: Recent works have discovered a relatively tight correlation between Ωm and the properties of individual simulated galaxies. Because of this, it has been shown that constraints on Ωm can be placed using the properties of individual galaxies while accounting for uncertainties in astrophysical processes such as feedback from supernovae and active galactic nuclei. In this work, we quantify whether using the properties of multiple galaxies simultaneously can tighten those constraints. For this, we train neural netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…In our case, for simplicity, we decided to optimize it. 17 https://optuna.org 18 We note that there are more powerful statistics tests than the ones presented here, but we employ them as a way to compare with previous works (Villaescusa-Navarro et al 2022;Chawak et al 2024;Echeverri-Rojas et al 2023) that used these metrics due to the different inference method.…”
Section: Degeneraciesmentioning
confidence: 99%
See 2 more Smart Citations
“…In our case, for simplicity, we decided to optimize it. 17 https://optuna.org 18 We note that there are more powerful statistics tests than the ones presented here, but we employ them as a way to compare with previous works (Villaescusa-Navarro et al 2022;Chawak et al 2024;Echeverri-Rojas et al 2023) that used these metrics due to the different inference method.…”
Section: Degeneraciesmentioning
confidence: 99%
“…Recent works have identified the existence of a tight correlation between the fraction of matter in the total matter density of our Universe Ω m and the properties of individual galaxies in state-of-the-art hydrodynamic simulations (Villaescusa-Navarro et al 2022;Chawak et al 2024;Echeverri-Rojas et al 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, relying on machine learning, Villaescusa-Navarro et al (2022) extracted cosmological constraints from the properties of one galaxy. Subsequently, Chawak et al (2024) showed that constraints can be improved when using multiple galaxies. This method has also been tested in Echeverri-Rojas et al (2023) using four different simulations, including IllustrisTNG (Marinacci et al 2018;Naiman et al 2018;Springel et al 2018;Nelson et al 2019), SIMBA (Davé et al 2019), Astrid (Bird et al 2022;Ni et al 2022Ni et al , 2023, and Magneticum (Dolag 2015).…”
Section: Introductionmentioning
confidence: 99%